Perceived health related risks of vaping among undergraduate students in Faculty of Medicine and Health Sciences, Universiti Putra Malaysia - Minhat, Halimatus Sakdiah; S., Selvanathan; N., Abdul Wahab (Community Health Society Malaysia, 2017)
Background: Vaping has become a new trend used by people globally. This study aimed to determine the perceived health risks of vaping and the associated factors among undergraduate health-related students in Universiti Putra Malaysia (UPM). Materials and Methods: A cross-sectional study was conducted among 570 undergraduate students in Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (UPM), Serdang. The respondents were those who were enrolled in the Doctor of Medicine, Bachelor in Nursing, Bachelor of Science (Environmental and Occupational Health), Bachelor of Science (Biomedicine), Bachelor of Science (Nutrition and Community Health) and Bachelor of Science (Dietetics) programmes. Data was collected using validated self-administered questionnaire. Statistical significance was considered at p – value < 0.05 (with a confidence limit at 95 %). Result: Majority of the respondents were young adults (97.9%), female (65.6%), Malay (72.4%), non-smoker (94.4%), had poor knowledge on health-related risks of vaping (59.1%), had more favourable attitude towards vaping (52.1%), were not influenced by mass media (56.7%) and perceived vaping as harmful (51.9%). Factors were significantly associated with perceptions towards health related risks of vaping were gender (X2= 11.504, p=0.001), knowledge (X2=8.408, p=0.004) and attitude (X2= 20.179, p<0.001). Conclusion: The students perceived vaping as harmful and had more favourable attitude towards vaping. However, the knowledge related to health related risks of vaping was poor despite being medical and health sciences students which reflects the need for more programmes to create better awareness and knowledge which may include the use mass media as a medium to deliver the information.